2019
DOI: 10.3389/fpsyg.2019.01249
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Measurement Invariance of Scales Assessing Stigma and Attitude to Seeking Professional Psychological Help

Abstract: There has been a growing interest in research on stigma and attitude toward psychotherapy, and these variables are expected to show cross-cultural variations. The Stigma Scale for Receiving Psychological Help (SSRPH), the Self-Stigma of Seeking Help (SSOSH) and the Inventory of Attitudes to Seeking Mental Health Services (IASMHS) are widely used and this study examined their measurement invariance as this is a prerequisite for use in cross-cultural studies. Data were collected online from groups of Chinese stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The online data used in the present study are from a dataset collected in a project for intercultural comparison of willingness to seek psychological help [43]. The data were collected in Germany and China in August 2016 and the collection lasted for 6 months.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The online data used in the present study are from a dataset collected in a project for intercultural comparison of willingness to seek psychological help [43]. The data were collected in Germany and China in August 2016 and the collection lasted for 6 months.…”
Section: Participantsmentioning
confidence: 99%
“…The results of the comparison between the underlying structure and the invariant items of the scales remained unchanged. Therefore, we presented the results without conducting propensity score matching, owing to the large sample size" [43].…”
Section: Gad-7mentioning
confidence: 99%
“…Respondents rate the degree they agree or disagree with each item using a 5-point Likert-scale format from 1 (strongly disagree) to 3 (agree and disagree equally) to 5 (strongly agree). Cronbach’s alpha of the Chinese-version scale was 0.71 in previous study (Zhou et al, 2019 ). The scale reliability in the current study was good (Cronbach’s α = 0.85).…”
Section: Methodsmentioning
confidence: 67%
“…Responses on this scale were rated on a 5-point Likert-type scale ranging from 1 (strongly disagree) to 3 (agree and disagree equally) to 5 (strongly agree). The Chinese version of this scale demonstrated good reliability (Cronbach’s alpha = 0.82) (Zhou, Lemmer, Xu, & Rief, 2019 ). The Cronbach’s α in the current study was 0.80.…”
Section: Methodsmentioning
confidence: 99%
“…The authors suppose a onefactor structure for the questionnaire which was mainly confirmed cross culturally [124] or at least partly replicated [117]. Cross cultural invariance was proofed for a German sample [125] while it is still lacking for Latin American samples. Thus, only the sum score was used for analyses.…”
Section: Methodsmentioning
confidence: 93%